How communication approaches impact mergers and acquisitions outcomes. Issue 20 (12th November 2016) - Angwin, Duncan N.; Mellahi, Kamel; Gomes, Emanuel; Peter, Emmanuel
Abstract : Communication is generally viewed as a critical component in mergers and acquisitions (M&A) performance, yet surprisingly little research has examined the link between different communication approaches and M&A outcomes. This paper provides a systematic empirical study to evaluate the link between communication approaches and M&As outcome. Specifically, a typology is created to examine interaction between the process and content of communication and M&A outcomes, in terms of employee commitment to merged organization strategy and M&A survival. Using data drawn from a single clearly defined M&A wave in the Nigerian banking sector, different communication practices are related to M&A outcomes. The findings are the first to show the effects of communications practices in African M&A and answer the calls for extending M&A research beyond western developed countries. They confirm the importance of communication practices in M&A, extend earlier findings on the importance of post-acquisition integration communication in US and European contexts and show the importance of communicating throughout the whole M&A process.